Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.